The gold rush in the Yanomami Indigenous Land: mining and the Haximu genocide - Dalmonego, Corrado; Oliveira, Márcia Maria de; Roberti Junior, João Paulo; Reis, Tiago Siqueira (Argumentum, 2024)
This study investigates the gold rush in the Yanomami Indigenous Land between 1987 and 1993. It examines the events, causes, developments, and implications of what should be considered one of the worst chapters in the history of relationships between indigenous communities and the impacts of mineral exploration on indigenous land. It highlights that one of the darkest results of the process of the invasion of Yanomami territory manifested itself in the Haximu genocide in 1993. The study sheds light on the understanding of the recurring processes of violence suffered by the Yanomami, which are still little known by the general population.
Keywords: Gold Rush; Yanomami; Haximu Genocide; Prospectors